Spectroscopic and Thermal Analysis of Mixed Ligand Complexes of Iron(III) and Copper(II) Derived fro - El-Zwaey, R.S.; El-Ajaily, M.M.; Maihub, A.A. (Asian Journal of Chemistry, 2010)
Two new mixed ligand complexes of Fe(III) and Cu(II) with catechol and benzil ligands have been prepared and characterized. The probable structures of the complexes have been elucidated on the basis of elemental analyses, molar conductance, thermogravimetric analysis, magnetic moments, infrared, electron paramagnetic resonance, electronic adsorption and mass spectra. The elemental analysis data reveal the formation of 2:1:1 [M:L1:L2] complexes. The molar conductance measurements show the presence of a non-electrolytic nature. The thermogravimetric analysis data of both complexes display the existence of hydrated and coordinated water molecules. The magnetic moments exhibit a paramagnetic resonance spectra of the complexes under investigation show the existence of a paramagnetic phenomena which support their geometrical structures. The infrared spectral data were agreed with the coordination sites of the free ligand with the central metal ion through –OH and C=O groups. The electronic adsorption spectral results display the electronic transitions of the ligand and suggest an octahedral structure for Fe(III) complex and a square planar geometry for Cu(II) complex. The mass spectrum of Fe(III) complex shows the fragmentation process (m/e+) for this complex.